Early revision rate in robotic-assisted total knee arthroplasty compared to conventional total knee arthroplasty based on the Finnish Arthroplasty Register in prospective cohort study - Sylvestersson, Emil (My University, 2026)
Total knee arthroplasty (TKA) is an effective treatment for relieving pain in advanced knee osteoarthritis. Robotic-assisted total knee arthroplasty (rTKA) has been introduced to improve surgical precision and outcomes, but evidence on its effect on implant survival is limited. The aim of this study was to compare early implant survival between rTKA and conventional total knee arthroplasty (cTKA). The survival endpoint was the first revision. Revisions due to periprosthetic joint infection (PJI), or due to reasons other than PJI were considered as secondary endpoints. Using data from the Finnish Arthroplasty Register (FAR) and the Care Register for Health Care (HILMO), all 1,347 MAKO rTKAs performed in Finland up to May 2023 were identified and compared with 40,274 cTKAs using the same Triathlon implant system between 2014 and 2023. At one year, Kaplan–Meier revision-free survival was 99.1% for rTKA and 98.5% for cTKA. There were 10 revisions in the rTKA group and 603 in the cTKA group, with PJI being the most common cause of revision in both cohorts. Cox regression analyses suggested a borderline significant reduction in revision risk with rTKA compared to cTKA, particularly within the first three months after the index surgery. A similar borderline reduction was observed for revisions due to PJI, while no difference was found for revisions due to other causes. Based on the results, early implant survival after rTKA was at least as good as after cTKA.
Keywords: Total knee arthroplasty (TKA), robotic-assisted total knee arthroplasty (rTKA), conventional total knee arthroplasty (cTKA), revision arthroplasty, prosthetic complication, periprosthetic infection